Chaucer’s Choices - Stadnik, Katarzyna (Peter Lang GmbH, 2015)
The monograph discusses the relation between language and visual culture, focusing on two Chaucerian narratives, «Knight’s Tale» and «Troilus and Criseyde». The study highlights the significance of the continuity of imagery in language and material culture for cultural transmission, providing insights into the relation between Chaucer’s linguistic usage and the late medieval symbolic tradition. Undertaken within the Cognitive Linguistic framework, the research indicates the usefulness of adopting a panchronic perspective on the development of language and culture.
10.3726/978-3-653-05874-1
Keywords: Chaucer; Geoffrey; Troilus and Criseyde; The knight's tale; Sprache; Symbol; Tradition; Kognition